A critique on "A cell model of effective thermal conductivity for saturated porous media". (September 2021) - Janssen, Hans
Highlights: comment on a thermal conductivity model for porous media published in this journal. it is shown that the presented cell model is conceptually and practically erroneous. as it may yield conductivities outside of the theoretical bounds for porous material. and as it has a poor performance for dry materials, contrary to the paper's outcome. the poor performance remained hidden due to the use of incorrect air conductivities. Abstract: In August 2019, this journal published the paper "A cell model of effective thermal conductivity for saturated porous media" (Zhu, 2019), which develops and validates a new analytical prediction model for the thermal conductivities of saturated porous materials. This critique reveals that the model is conceptually and practically flawed, by on the one hand showing that it may result in thermal conductivities outside of the series and parallel limits and by on the other hand exposing its poor performance for dry porous media contrary to Zhu's positive outcomes. Given that these flaws, if known to the author and/or reviewers, would (probably) have led them to a "not fit for publication" evaluation, the discusser suggests an official retraction of (Zhu, 2019).